Evaluation of electrical conductivity of maize flour by ohmic heating - KAUR, NIMRATBIR; SINGH, A K; CHOPRA, SANGEETA (The Indian Journal of Agricultural Sciences, 2015)
Electrical conductivity of foods is key component in the design of an ohmic heater. Electrical conductivities of maize flour of three particle sizes ( 0.6 mm, 1.0 mm and 1.4 mm) at different moisture contents (40%, 35% , 30% and 25%) and applied voltage gradient (55V/cm, 45V/cm, 35V/cm and 25V/cm) were determined, the samples were heated for 90 seconds. In general maize flour at 40% moisture content was more conductive than samples prepared with 35%, 30% and 25% moisture content. The effect of applied voltage gradient was significant at all the four moisture contents. At 40% moisture content, conductivity was highest for 55V/cm and minimum for 25V/cm. The effects of applied voltage were considerable for samples with 35% and 30% moisture content but for 25% the effect was least significant. Samples with smaller particle size were more conductive than larger particle size flour at all the voltage and moisture content combinations. In all cases, electrical conductivities increased linearly with temperature till the gelatinization temperature.